Genetic survey of alveolar and cystic echinococcoses in Romania: first molecular evidence of Echinococcus multilocularis in humans in the country - Šnábel, V.; Calma, C.; Georgescu, S. O.; CAVALLERO, Serena; D'AMELIO, Stefano; Vasilková, Z.; Ito, A. (Helminthologia, 2017)
Cystic echinococcosis (CE) and alveolar echinococcosis (AE) are considered as one of the most important zoonotic diseases in Romania, where they are subject to mandatory reporting. To obtain more knowledge about the genetic diversity of causative agents of these diseases, 11 isolates from humans and ungulate intermediate hosts from the two regions of Romania were genotyped using mitochondrial markers. In clinical samples of five patients from north-eastern Romania (Iasi, Botosani, Vaslui counties), was identified as causal agent by sequence analysis. To the best of our knowledge this finding presents the first molecular evidence of in humans from Romania. Only two cases of AE in patients were previously documented in the country by serological methods. In our four patients the most widespread European variant E5 of was recorded, whereas in isolate from Vaslui county three nucleotide substitutions were detected as compared to the most related E5 haplotype. One of these mutations (411T/G) matched N1 and N2 haplotypes described previously from North America. In six CE samples retrieved from western Romania (Caras-Severin and Timis counties), two human isolates were diagnosed as G7, one as s.s. G1 and one as s.s. G3 using and sequencing. In ungulates, the cattle isolate was allocated to s.s. G1 and pig isolate to G7. The two G7 findings in humans reinforced the recent view that G7 was underestimated as compared to the s.s. regarding human CE threat that can be further employed for identifying sources of infections and establishing suitable preventive measures.